2022
DOI: 10.55493/5002.v12i7.4553
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Financial Performance in the Banking Sector: A Case Study of Listed Kuwaiti Banks

Abstract: This study explores the determinants of the profitability of banks listed on the Kuwaiti stock exchange, Boursa Kuwait. This study also investigates the financial performance of the listed Kuwaiti banks during the COVID-19 pandemic. The aim of this study is to examine the correlation between profitability and the factors that determine profitability for 11 listed Kuwaiti banks from 2013 to 2020. Relevant data was statistically analyzed using the generalized method of moments (GMM) model. The empirical findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…They found that among the important indicators of firm performance are investor sentiment and insider ownership. Alharthi (2022) emphasize the importance of deposit volume and oil prices on Kuwaiti banking sector performance.…”
Section: Literature Reviewmentioning
confidence: 98%
“…They found that among the important indicators of firm performance are investor sentiment and insider ownership. Alharthi (2022) emphasize the importance of deposit volume and oil prices on Kuwaiti banking sector performance.…”
Section: Literature Reviewmentioning
confidence: 98%